Efeitos do microcrédito rural sobre a produção agropecuária: evidências do programa agroamigo - Guedes, Isabela Assis (2017)
The purpose of this study was to analyze the effect of rural microcredit on the value of agricultural production in the municipalities of Northeastern Brazil assisted by Agroamigo from 2005 to 2015, considering the volume of resources and the time of exposure of municipalities to the Program . For that, was used the Differences in Differences (Dd) method with control for ﬁxed effect. Based on the analysis, it was possible to identify that rural microcredit had a positive, although very small, of 0.10 % for six years of exposure and effect only on the value of livestock production. In agriculture and in the total set of agricultural production, no positive relationship was identiﬁed between the time of exposure to the Program and the increase in the production value of the municipalities covered by Agroamigo. The study also presented evidence that, although there is a considerable amount of resources directed to the production of family farmers, the value of the investment that returns to society is still very low. The results showed no evidence that the rural microcredit program Agroamigo is capable of generating a signiﬁcant change in the economic dimension with regard to family agriculture. Thus, many challenges and advances are being faced to consolidate rural microcredit as a tool that contributes effectively to increasing agricultural production in a sustainable way, speciﬁcally in the Northeast of Brazil.